Mechanical Stimulation-Induced Calcium Signaling by Piezo1 Channel Activation in Human Odontoblast Reduces Dentin Mineralization - Matsunaga, Mayumi; Kimura, Maki; Ouchi, Takehito; Nakamura, Takashi; Ohyama, Sadao; Ando, Masayuki; Nomura, Sachie; Azuma, Toshifumi; Ichinohe, Tatsuya; Shibukawa, Yoshiyuki (Frontiers in Physiology, 2021)
Odontoblasts play critical roles in dentin formation and sensory transduction following stimuli on the dentin surface. Exogenous stimuli to the dentin surface elicit dentinal sensitivity through the movement of fluids in dentinal tubules, resulting in cellular deformation. Recently, Piezo1 channels have been implicated in mechanosensitive processes, as well as Ca2+ signals in odontoblasts. However, in human odontoblasts, the cellular responses induced by mechanical stimulation, Piezo1 channel expression, and its pharmacological properties remain unclear. In the present study, we examined functional expression of the Piezo1 channel by recording direct mechanical stimulation-induced Ca2+ signaling in dentin matrix protein 1-, nestin-, and dentin sialophosphoprotein-immunopositive human odontoblasts. Mechanical stimulation of human odontoblasts transiently increased intracellular free calcium concentration ([Ca2+]i). Application of repeated mechanical stimulation to human odontoblasts resulted in repeated transient [Ca2+]i increases, but did not show any desensitizing effects on [Ca2+]i increases. We also observed a transient [Ca2+]i increase in the neighboring odontoblasts to the stimulated cells during mechanical stimulation, showing a decrease in [Ca2+]i with an increasing distance from the mechanically stimulated cells. Application of Yoda1 transiently increased [Ca2+]i. This increase was inhibited by application of Gd3+ and Dooku1, respectively. Mechanical stimulation-induced [Ca2+]i increase was also inhibited by application of Gd3+ or Dooku1. When Piezo1 channels in human odontoblasts were knocked down by gene silencing with short hairpin RNA (shRNA), mechanical stimulation-induced [Ca2+]i responses were almost completely abolished. Piezo1 channel knockdown attenuated the number of Piezo1-immunopositive cells in the immunofluorescence analysis, while no effects were observed in Piezo2-immunopositive cells. Alizarin red staining distinctly showed that pharmacological activation of Piezo1 channels by Yoda1 significantly suppressed mineralization, and shRNA-mediated knockdown of Piezo1 also significantly enhanced mineralization. These results suggest that mechanical stimulation predominantly activates intracellular Ca2+ signaling via Piezo1 channel opening, rather than Piezo2 channels, and the Ca2+ signal establishes intercellular odontoblast-odontoblast communication. In addition, Piezo1 channel activation participates in the reduction of dentinogenesis. Thus, the intracellular Ca2+ signaling pathway mediated by Piezo1 channels could contribute to cellular function in human odontoblasts in two ways: (1) generating dentinal sensitivity, and (2) suppressing physiological/reactional dentinogenesis, following cellular deformation induced by hydrodynamic forces inside dentinal tubules.